2022
DOI: 10.1007/s13760-022-02104-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of LSVT-BIG via telerehabilitation on non-motor and motor symptoms and quality of life in Parkinson’s disease

Abstract: Background Parkinson's disease (PD) is a neurodegenerative disease with motor and non-motor symptoms affecting the quality of life. This study aimed to investigate the effects of the Lee Silverman Voice Therapy (LSVT)-BIG rehabilitation program via telerehabilitation on quality of life, motor and non-motor symptoms in people with Parkinson's disease (PwPD), and their correlation with each other. Methods Fifteen patients with mild-to-moderate PD (Hoehn and Yahr stages 1-3) were included in the LSVT-BIG exercise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…They also found that all three exercise programs were effective in improving motor symptoms. Additionally, a lot of case studies found that LSVT BIG training improved functional mobility (Fishel et al, 2020;Flood et al, 2020;Hirakawa et al, 2022;Janssens et al, 2014), gait speed (Flood et al, 2020;Kleppang & Jørgensen, 2020;Millage et al, 2017), stride length (Flood et al, 2020), and motor symptoms (Fırat et al, 2023;Hirakawa et al, 2022;Iwai et al, 2021;Janssens et al, 2014;McDonnell et al, 2018;Millage et al, 2017;Ueno et al, 2017 (Fox et al, 2012). A review found results supporting that the online modified version of LSVT LOUD is not inferior to the standard protocol (Herd et al, 2012).…”
Section: Pretestmentioning
confidence: 99%
See 1 more Smart Citation
“…They also found that all three exercise programs were effective in improving motor symptoms. Additionally, a lot of case studies found that LSVT BIG training improved functional mobility (Fishel et al, 2020;Flood et al, 2020;Hirakawa et al, 2022;Janssens et al, 2014), gait speed (Flood et al, 2020;Kleppang & Jørgensen, 2020;Millage et al, 2017), stride length (Flood et al, 2020), and motor symptoms (Fırat et al, 2023;Hirakawa et al, 2022;Iwai et al, 2021;Janssens et al, 2014;McDonnell et al, 2018;Millage et al, 2017;Ueno et al, 2017 (Fox et al, 2012). A review found results supporting that the online modified version of LSVT LOUD is not inferior to the standard protocol (Herd et al, 2012).…”
Section: Pretestmentioning
confidence: 99%
“…Recently, a technique named “LSVT BIG” derived from Lee Silverman Voice Therapy (LSVT LOUD) has been shown to improve motor performance (Ebersbach et al., 2010 , 2015 ; Farley et al., 2008 ; Fırat et al., 2023 ), gait (Ebersbach et al., 2015 ; Farley & Koshland, 2005 ), and reach (Farley & Koshland, 2005 ), ADL (Fırat et al., 2023 ), and QoL (Fırat et al., 2023 ) in PD. LSVT BIG training aims to recalibrate the sensory perception of the normal amplitude of movements while focusing on high‐amplitude movements with multiple repetitions, high intensity, and increasing complexity.…”
Section: Introductionmentioning
confidence: 99%
“…There are different treatment modalities available to manage PD-related symptoms that result in improvement of the QOL in this patient group [ 12 , 13 ]. Failure to address QOL issues leads to negative consequences for the individual and their family.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, studies evaluating physical therapy services using telerehabilitation generally include individuals with idiopathic PD aged 50-75, between Hoehn & Yahr stages I-III, within 2-10 years of diagnosis, and without evidence of dementia. The types of exercise with remote delivery or supervision varied significantly (e.g., dance [4], amplitude-based movement training [5,10], postural stability training with virtual reality [6], aerobic exercise via cycling [7], mindfulness yoga [11], coordinated multidisciplinary care [12], Badajuajin Quiigong [13], generalized physiotherapy exercises [8,9]). Safety was demonstrated in remote sessions delivered to either a group [4] or individually [5][6][7]9].…”
mentioning
confidence: 99%
“…Seidler et al [4] noted improvements in balance and motor sign severity when comparing a remotelydelivered, group-based dance intervention compared to in-person delivery. A cohort study of remotelydelivered amplitude-based movement training using the LSVT BIG paradigm demonstrated improvements in motor sign severity, subjective activities of daily living (ADL) performance, and quality of life [10]. A case study of the same remotelydelivered intervention reported improvements in gait, endurance, balance confidence, and quality of life in a 67-year-old woman with PD [5].…”
mentioning
confidence: 99%